The Taso Research Program: Retrospect and Prospect - George, Peter; Preston, Richard J. (Anthropologica, 2022)
Collaborative interdisciplinary research teams are still relatively unusual within the social sciences. Teams that combine both social and physical scientists are even more rare. Yet there are major research opportunities and challenges offered when distinct, yet complementary, foci of expertise are brought to bear on a common empirical problem. In this paper, we begin by introducing McMaster University’s Research Program for Technology Assessment in Subarctic Ontario (TASO). We summarize briefly the first phase of these research activities in Northern Ontario, and its accomplishments, and outline the projected second phase of our research which is focussed on community economic and social development am